(untitled) (International Journal of Mathematics and Physics, 2013)
We present recent results on general relativistic uniformly rotating white dwarfs. Namely, on the basis of the general relativistic Feynman-Metropolis-Teller theory for white dwarfs we focus on delayed type Ia supernova explosions and gravitational collapses of super-Chandrasekhar mass white dwarfs, where we estimate so called «spinning down» time scale (lifetime) due to the electromagnetic radiation.